The Reality of the Employment of the Educational Technology in the Educational Process in the Schools of Kasabah AL Mafraq from the Teacher’s Perspective - Al-Shdefait, Muneera Abd Al Kareem; Al-Zboon, Mohammad Saleem (Dirasat: Educational Sciences, 2020)
The aim of the study is to identify the reality of employing educational technology in the educational process at schools of Kasbah Al Mafraq from teachers’ perspective. To achieve this goal, a descriptive approach was used, where a questionnaire was exploited, which consisted of three areas (knowledge, skills, and evaluation) with 22 paragraphs. The questionnaire’s validity and stability was verified, and then it was distributed to the sample of the study which consisted of 360 teachers from the schools of Kasabah AL Mafraq. The results of the study showed that the employment of educational technology in the educational process, from the teachers’ perspective was poor and with an average arithmetic (2.17). The results also showed no significant differences in the evaluations of the study sample for the reality of the employment of educational technology in the educational process from the teacher’s perspective due to gender and qualification variables. In light of the results, the researchers recommend that the Jordanian Ministry of Education should hold more specialized training courses and workshops in the field of educational technology, encourage teachers to use these courses in the educational process, and raise awareness among teachers and students about the positive use of modern technology in learning.